High-growth firms in Georgia - Taelim Choi; John C. Robertson; Anil Rupasingha (Federal Reserve Bank of Atlanta, 2013)
This paper reports the results of a study of the characteristics and direct employment impact of high-growth firms operating in Georgia. The longitudinal data used in this study are from the National Establishment Time-Series (NETS) database. Using a standard definition of high employment growth to classify firms, we track the direct employment contribution of high-growth firms in the state from 1989 to 2009. We find that only a small fraction of firms satisfied the high-growth employment criteria in any year, but these rapidly growing firms made a disproportionately large contribution to overall job creation in the state. We discover that, as has been found for the United States as a whole, the number of high-growth firms and their average job creation has declined during last decade. We also find that the incidence of high growth and the resulting job creation differ significantly according to size, age, industry, type of organizational structure, and ownership as well as location. A separate analysis focusing on firms with rapid sales revenue growth reveals that firms with fast-growing revenue- are not necessarily firms with fast-growing employment.
Keywords: R11; R12; 330; high-growth firms; NETS data; job creation; firm age; firm size; industry; organizational structure; business dynamics; location